A new processing method of CaZn2(OH)(6)center dot 2H(2)O powders: Photoluminescence and growth mechanism - Xavier, C. S. [UNESP]; Sczancoski, J. C.; Cavalcante, L. S.; Paiva-Santos, C. O. [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP]; Li, M. Siu (Elsevier B.V., 2009)
In this communication, we report on the formation of calcium hexahydroxodizincate dehydrate, CaZn2(OH)(6)center dot 2H(2)O (CZO) powders under microwave-hydrothermal (MH) conditions. These powders were analyzed by X-ray diffraction (XRD), Field-emission gum scanning electron microscopy (FEG-SEM), ultraviolet-visible (UV-vis) absorption spectroscopy and photoluminescence (PL) measurements. XRD patterns confirmed that the pure CZO phase was obtained after MH processing performed at 130 degrees C for 2 h. FEG-SEM micrographs indicated that the morphological modifications as well as the growth of CZO microparticles are governed by Ostwald-ripening and coalescence mechanisms. UV-vis spectra showed that this material have an indirect optical band gap. The pure CZO powders exhibited an yellow PL emission when excited by 350 nm wavelength at room temperature. (C) 2009 Elsevier Masson SAS. All rights reserved.
Keywords: CaZn2(OH)(6)center dot 2H(2)O; Lozenge; Rietveld refinement; Crystal growth; Photoluminescence